PELATIHAN GELAS AWI DALAM MENINGKATKAN LIFE SKILL WARGA BELAJAR DI PKBM BUANA MEKAR - Sodik, Firman Ja’far; Danugiri, Dadang; Santika, Tika (Jurnal Pendidikan Luar Sekolah, 2022)
Abstract Every human resource development (HR) has several factors, one of which is education. Non-formal education is an educational path outside of formal education which is carried out in stages and in a structured manner. PKBM is a vehicle to increase the knowledge and economy of learning citizens. The glass awi training is one of the trainings contained in the Mekar Buana PKBM. This study aims to describe the process and results of the glass awi training in improving the life skills of learning residents at PKBM Buana Mekar. This research uses a qualitative approach with a case study method. This research was conducted at PKBM Buana Mekar. The subjects in the study consisted of PKBM managers and one tutor, two learning residents. The research data were obtained through observation, interviews, and documentation studies. The results of the study show that seeing a lot of potential for learning citizens in entrepreneurship and to improve the life skills of learning citizens. The learning process is carried out in one day and the activities are going well using participatory learning strategies, the suggestions and infrastructure are quite adequate. Learning residents are able to distinguish between types of awi, changes in the attitudes of learning residents regarding socialization and empathy. Training activities are able to improve the life skills of learning residents at PKBM Abstrak Setiap pembangunan sumber daya manusia (SDM) ada bebarapa faktor salah satunya pendidikan. Pendidikan non formal adalah sebuah jalur pendidikan di luar dari pendidikan formal yang dilaksanakan secara berjenjang da terstruktur. PKBM adalah wahana untuk meningkatkan pengetahuan dan ekonomi warga belajar. Pelatihan gelas awi merupakan salah satu pelatihan yang terdapat dalam PKBM Mekar Buana. Penelitian ini bertujuan untuk Mendeskripsikan proses dan hasil pelatihan gelas awi dalam meningkatkan life skill warga belajar di PKBM Buana Mekar. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Penelitian ini dilakukan di PKBM Buana Mekar. Subjek dalam penelitian terdiri dari pengelola PKBM dan satu tutor,dua warga belajar. Data penelitian diperoleh melalui teknik observasi, wawancara, dan studi dokumentasi. Hasil penelitian menunjukan bahwa melihat banyak potensi warga belajar dalam berwirausaha dan untuk meningkatkan life skill para warga belajar. Proses pembelajar dilakuka satu hari dan kegiatan berjalan dengan baik dengan menggunakan strategi pembelajaran partisipatif, saran dan prasarana cukup memadai. Warga belajar mampu membedakan jenis awi, perubahan sikap warga belajar terkait sosialisasi dan sikap empati. Kegiatan pelatihan mampu meningkatkan life skill warga belajar di PKBM Mekar Buana